Digitalization and Strategies to Optimize the Use of Information Technology in The Supervision of Firearms Ownership Data Collection - Alam, Seala Syah (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2024)
The ownership of firearms among Soldier and Police has become an important issue. It began with the arrest of a former TNI member who ordered an unknown person to buy illegal firearms, which empirically proves that illegal firearms are freely traded from some unscrupulous members of TNI and Polri. The conventional way of controlling data collection of weapons in DitIntelkam, which involves some complicated procedures along with long stages and time consuming, is presumed to be one of the factors of many firearms owners are unwilling to register their firearms. This research aims to describe the use of information technology digitalization to control firearms ownership and reduce the number of shootings using unregistered firearms. The research method is descriptive-qualitative by involving research informants and observations towards the supervision of data collection in DitIntelkam Polda Metro Jaya. The finding of this research shows that DitIntelkam should change their approach from the conventional way to the application of digitalization based on Information Technology to optimize the supervision of firearms data collection, especially at DitIntelkam Polda Metro Jaya.